Representing affective labour and gender performativity in knowledge work: a multimodal critical discourse analysis. (26th September 2016) - Roderick, Ian
Abstract : This paper argues that a multimodal approach to critical discourse analysis makes visible how contemporary office design and furnishings prescribe gender performativities crucial to the labour of communicative capitalism (Dean 2005). Examining WWW-based promotional material produced by multinational contract furniture producers, a critical analysis is offered of the ways in which the open-plan office is represented as a wellspring of affective labour. First, attention is turned to detailing the kinds of social actors and their actions depicted in the representations of office work. Second, the kinds of interactional meanings produced in the videos are documented. Having established how these idealized representations of knowledge work highlight particular embodiments and actions, the paper then argues that the promotional materials are in fact constituting those 'bodies that matter' (Butler 1993) to communicative capitalism. Ultimately, these videos depict how the female knowledge worker must 'cite' a normative feminized affective worker so as to be recognized as a viable employee.